Restricting Polyoxometalate Movement Within Metal-Organic Frameworks to Assess the Role of Residual Water in Catalytic Thioether Oxidation Using These Dynamic Composites - Buru, Cassandra T.; Lyu, Jiafei; Liu, Jian; Farha, Omar K. (Frontiers in Materials, 2019)
Comprised of high valent metal centers connected via oxide bonds, polyoxometalates (POMs) have a rich history in redox reactions. These discrete metal oxide clusters often are immobilized on heterogeneous supports to increase stability and allow for recyclability for catalytic reactions. One such support is the metal–organic framework (MOF), NU-1000. When POMs are installed into NU-1000, they are first sited in the mesoporous channel. Upon application of heat and removal of some physisorbed water, the POMs migrate to the microporous channel, where some active sites are blocked by the MOF linkers, resulting in lowered catalytic activity. To restrict this movement from the mesopore, we report here the use of two MOFs, naphthalene dicarboxylate-modified NU-1000 (NU-1000-NDC) and NU-1008, as supports for the Keggin-type polyoxometalate (POM), H3PW12O40. Upon the application of heat, these frameworks were found to hinder or prevent the movement of the POM between channels by blocking the aperture(s) connecting the mesoporous and microporous channels. The composite POM@MOF materials were used for the oxidation of a mustard gas simulant, 2-cholorethyl ethyl sulfide, using H2O2 as the oxidant. The POM@MOF catalysts exhibit enhanced reactivity when compared to the POM or MOF alone, more than doubling the initial rates. The activity trend in PW12@NU-1000-NDC matched that in PW12@NU-1000, where the scCO2-activated sample poised the POM in the mesopores to give greater substrate accessibility and enhance the reaction rate compared to the heated sample where the POMs are poised in the micropores. Contrary to these observed trends, PW12@NU-1008 prohibits POM migration and performs superior when water has been removed at elevated temperatures as the active sites are more accessible in the mesoporous channel.